Method for preparing a complex metal-oxide/silicon photocathode integrated with lanthanide upconversion nanoparticles at the interface - Dikhanbayev, К.; Rahimbekova, А.; Amze, М.; Yersin, А.; Batay, S.; Shabdan, Е. (Recent Contributions to Physics, 2025)
This study presents the fabrication of an integrated silicon photocathode based on a metal-oxide/silicon heterostructure. A SnO₂ thin film was deposited on the front surface of a p-n⁺-Si substrate via magnetron sputtering to enable UV photon absorption and corrosion protection. Lanthanide up-conversion nanoparticles (Ln-UCNPs, NaYF₄:Er³⁺@PbS) were integrated at the rear interface using spin-coating to convert near-infrared (NIR, 1550 nm) photons into visible light, achieving broad-spectrum absorption. SEM analysis confirmed the granular morphology of the SnO₂ layer (~140 nm thick) and the p-n⁺ junction depth (~0.6 µm). Current-voltage (I-V) measurements revealed enhanced tunneling charge transport and a Schottky barrier. Spectral response analysis demonstrated improved photosensitivity across 400–1100 nm, peaking at 870–900 nm. Photoelectrochemical (PEC) tests showed that Ln-UCNPs integration increased photocurrent density by ~5 times, significantly enhancing water splitting efficiency. This integrated structure offers a promising approach to improving the stability and spectral efficiency of Si-based photoelectrodes.
Keywords: metal oxide/silicon heterostructures; lanthanide up-conversion; photoelectrochemical water splitting; hydrogen energy